How self-help groups are empowering women amid out-migration: the groups are providing rural women with skills training leading to improved incomes as well as a greater say in local decision-making structures - Taneja, Garima; Bhattacharjee, Suchiradipta; Dikshit, Manya (International Water Management Institute, 2024)
Out-migration is a prominent trend in Pithoragarh district in the state of Uttarakhand. Young and educated men are increasingly migrating to other states seeking better employment opportunities. Young women are left with the children and the elders to look after the home and the farm.